Special electromagnetic field-treated water and far-infrared radiation alleviates lipopolysaccharide-induced acute respiratory distress syndrome in rats by regulating haptoglobin. Issue 1 (1st January 2021) - Luo, Changyong; Li, Yan; Liang, Xu; Chen, Yifan; Zou, Qiao; Kong, Yurong; Guo, Zhengguang; Sun, Wei; Wang, Xin
ABSTRACT: Special electromagnetic field-treated water (SEW) and far-infrared radiation (FIR) can reduce acute respiratory distress syndrome (ARDS) in rats inflicted by lipopolysaccharides (LPSs). However, little is known about its underlying molecular mechanism. Differentially expressed proteins (DEPs) of SEW and FIR interventions were obtained from a proteomics database. A total of 89 DEPs were identified. Enrichment analysis of DEPs was performed using the Database for Annotation, Visualization, and Integrated Discovery. These DEPs were associated with the responses to LPSs, acute inflammation, extracellular exosomes, glucocorticoids, and electrical stimuli. The protein-protein interaction network was set up using the STRING database. Modular analysis was performed using MCODE in the Cytoscape software. Proteins Haptoglobin, Apolipoprotein B, Transthyretin, and Fatty acid binding protein 1 were among the core networks. A tail vein injection of LPS was used to establish the rat model with ARDS. Parallel reaction monitoring confirmed Hp protein expression. Inflammatory pathway factors were detected using an enzyme-linked immunosorbent assay. This indicates that SEW and FIR can be considered as potential clinical treatment methods for ARDS treatment and that their functional mechanisms are related to the ability of alleviating lung inflammation through Hp protein adjustment.